2014
DOI: 10.1002/ijc.28894
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma in HIV‐infected patients in South Africa: Multicohort study in the antiretroviral therapy era

Abstract: The incidence of Kaposi’s Sarcoma (KS) is high in South Africa but the impact of antiretroviral therapy (ART) is not well defined. We examined incidence and survival of KS in HIV-infected patients enrolled in South African ART programs. We analyzed data of three ART programs: Khayelitsha township and Tygerberg Hospital programs in Cape Town and Themba Lethu program in Johannesburg. We included patients aged >16 years. ART was defined as a regimen of at least three drugs. We estimated incidence rates of KS for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 45 publications
7
53
2
Order By: Relevance
“…We confirmed the findings of other studies that advanced KS stage [10,11,18,19] predicts mortality, while chemotherapy [8,20] increases the chance of survival in KS patients. Unlike other South African studies [16,21] , we found no gender differences in mortality. Our study showed that both chemotherapy and radiation therapy were associated with improved survival.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We confirmed the findings of other studies that advanced KS stage [10,11,18,19] predicts mortality, while chemotherapy [8,20] increases the chance of survival in KS patients. Unlike other South African studies [16,21] , we found no gender differences in mortality. Our study showed that both chemotherapy and radiation therapy were associated with improved survival.…”
Section: Discussioncontrasting
confidence: 99%
“…We found good survival rates of KS patients in routine care, treated with ART and chemotherapy (ABV or oral VP16) and/or radiotherapy for selected patients. The overall one-year survival rate of 78.5% is comparable to survival estimates from other South African studies [8,9,16] , including a clinical trial that used similar chemotherapy regimens [9] . An observational study in the U.S. estimated two-year survival rates comparable to what we found in the late ART period in South Africa (81% and 79%, respectively) [17] .…”
Section: Discussionsupporting
confidence: 68%
“…First, over the course of HIV infection, when is CD4 most predictive of KS risk? KS risk has been observed to be inversely associated with baseline, 22-24 recent/current, 11,25-30 and nadir 31 CD4, and positively associated with time duration with CD4<200 cells/μL, 32 with inconclusive evidence that recent/current CD4 is the best predictor. 11,26 …”
Section: Introductionmentioning
confidence: 99%
“…Three studies conducted in Africa found KS incidence rates between 138/100,000 and 340/100,000 person-years in patients treated with ART. 5;8;9 These estimates suggest that the risk of developing KS in patients on ART is still substantial. In order to effectively plan and implement measures to reduce the KS burden in Africa, more reliable information on the KS risk in patients on ART and associated risk factors is needed.…”
Section: Introductionmentioning
confidence: 99%